2004
DOI: 10.1038/sj.bjc.6602043
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosing melanoma patients entering American Joint Committee on Cancer stage IV, C-reactive protein in serum is superior to lactate dehydrogenase

Abstract: Lactate dehydrogenase (LDH) in serum has recently been introduced into the American Joint Committee on Cancer (AJCC) staging system for cutaneous melanoma because of its prognostic value. We hypothesised LDH to be of value in discriminating melanoma patients entering AJCC stage IV from patients staying in AJCC stages I, II or III. Lactate dehydrogenase was compared to the acute phase protein C-reactive protein (CRP), which we observed to reflect the course of melanoma metastasis in a previous report. In this p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
37
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(42 citation statements)
references
References 24 publications
(34 reference statements)
4
37
1
Order By: Relevance
“…Other published TIL ACT trials did not find this correlation (12,14,15). Elevated serum level of lactate dehydrogenase (LDH), a marker of disease activity and tumor burden (21,22) was negatively correlated with clinical response (P ¼ 0.013; 0.219 OR; 95% CI: 0.061-0.992).…”
Section: Intent-to-treat Analysismentioning
confidence: 90%
“…Other published TIL ACT trials did not find this correlation (12,14,15). Elevated serum level of lactate dehydrogenase (LDH), a marker of disease activity and tumor burden (21,22) was negatively correlated with clinical response (P ¼ 0.013; 0.219 OR; 95% CI: 0.061-0.992).…”
Section: Intent-to-treat Analysismentioning
confidence: 90%
“…53 The potential role of CRP as a mediator of immune tolerance is also interesting. CRP binds to phosphocholine in damaged membranes where it increases clearance of apoptotic cells and binds to nuclear antigens, and by masking autoantigens from the immune system or enhancing their clearance, CRP may prevent autoimmunity.…”
Section: Discussionmentioning
confidence: 99%
“…CrP was found to be an independent prognostic factor for survival (86). In one study, CrP was found to be superior to LDH in discriminating melanoma patients entering AJCC stage IV from patients remaining in AJCC stages I, II or III (82). CrP was detected with a sensitivity of 77% and specificity of 90% in determining the progression of disease into stage IV (82).…”
Section: C-reactive Protein (Crp)mentioning
confidence: 99%
“…This protein is produced as a non-specific acute phase response to almost all forms of inflammation (80). In a study of melanoma, CrP was assayed in human blood using an immunonephelometric technique on a protein system analyzer (82). elevated serum CRP levels along with IL-6 were associated with reduced survival in metastatic melanoma and resistance to IL-2 therapy (82)(83)(84)(85)(86).…”
Section: C-reactive Protein (Crp)mentioning
confidence: 99%